2007
DOI: 10.1002/art.22711
|View full text |Cite
|
Sign up to set email alerts
|

Global analyses of gene expression in early experimental osteoarthritis

Abstract: Objective. To analyze genome-wide changes in chondrocyte gene expression in a surgically induced model of early osteoarthritis (OA) in rats, to assess the similarity of this model to human OA, and to identify genes and mechanisms leading to OA pathogenesis.Methods. OA was surgically induced in 5 rats by anterior cruciate ligament transection and partial medial meniscectomy. Sham surgery was performed in 5 additional animals, which were used as controls. Both groups underwent 4 weeks of forced mobilization, 3 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
227
2
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(251 citation statements)
references
References 69 publications
21
227
2
1
Order By: Relevance
“…Such merging of data from the 2 strains effectively limits any differences attributable solely to strain-specific variation, which might be unrelated to OA, and provides the greatest statistical power. This analysis revealed 390 up-regulated and 272 down-regulated genes in the OA samples (Supplementary Table 2 A significant number of genes described in a recent editorial (7,(18)(19)(20)(21)(22) as being OA targets based on the results of microarray analysis of human OA and a rat model were also identified ( Figure 1I), providing further confirmation of the relevance of our preclinical STR/Ort mouse model to human OA. Among these genes, levels of mRNA for Col2a1, tissue inhibitor of metalloproteinases 1 (TIMP-1), MMP-13, and ADAMTS-4 were further investigated by qPCR and showed increased levels in AC samples from 40-weekold STR/Ort mice as compared to those from age- 3258 POULET ET AL matched CBA mice ( Figure 1H).…”
Section: Flow Cytometrysupporting
confidence: 72%
See 1 more Smart Citation
“…Such merging of data from the 2 strains effectively limits any differences attributable solely to strain-specific variation, which might be unrelated to OA, and provides the greatest statistical power. This analysis revealed 390 up-regulated and 272 down-regulated genes in the OA samples (Supplementary Table 2 A significant number of genes described in a recent editorial (7,(18)(19)(20)(21)(22) as being OA targets based on the results of microarray analysis of human OA and a rat model were also identified ( Figure 1I), providing further confirmation of the relevance of our preclinical STR/Ort mouse model to human OA. Among these genes, levels of mRNA for Col2a1, tissue inhibitor of metalloproteinases 1 (TIMP-1), MMP-13, and ADAMTS-4 were further investigated by qPCR and showed increased levels in AC samples from 40-weekold STR/Ort mice as compared to those from age- 3258 POULET ET AL matched CBA mice ( Figure 1H).…”
Section: Flow Cytometrysupporting
confidence: 72%
“…Mice were used in experiments at ages 8-10 weeks (young; 5 CBA and 6 STR/Ort mice), 18-20 weeks (mature; 5 CBA and 7 STR/Ort mice), and 40-42 weeks (aged; 9 CBA and 14 STR/Ort mice). Left knee tibial and femoral surfaces were exposed, and AC from each condyle was isolated using a Friedman-Pearson micro-rongeur (extra-fine tip, 0.7-mm cup width; Fine Science Tools) (7,13), and samples were kept in RNAlater (Qiagen). Right knees were processed for histologic examination.…”
Section: Methodsmentioning
confidence: 99%
“…Studies of the regulation of aggrecanases have shown that the cytokine interleukin-1 (IL-1) induces ADAMTS-5 to a lesser degree than ADAMTS-4, but given the disparity in aggrecanase activity, this may not reflect a lesser importance for ADAMTS-5 (5). Although metalloproteinase expression levels in end-stage OA showed that ADAMTS-5 was among the proteinases that are repressed at this time point (9), recent genome-wide microarray studies of a surgically induced OA in the rat have revealed that Adamts5 is upregulated 4 weeks after surgery (10). These data suggest that ADAMTS-5 is likely to be important in early aggrecan cleavage during the development of OA, but may be repressed, perhaps through a feedback mechanism, during late stages of OA.…”
Section: Jelena Gavrilovicmentioning
confidence: 99%
“…Studies of gene expression in OA, both genome wide (10,24,25) and of specific gene families (9), have revealed important pathways for further study. The article by Chia et al emphasizes the fact that development of OA may well result in modulation of the location and/or function of preexisting proteins in articular cartilage.…”
Section: Jelena Gavrilovicmentioning
confidence: 99%
“…In addition, well defined animal models (e.g., rats with surgically induced OA by anterior cruciate ligament transaction) may also assist in the discovery of novel disease pathways. Such approach was recently demonstrated at the RNA level to identify genes involved in OA pathogenesis [59]. Moreover, given the continuous growth in commercially available knock-out animals, such models may serve as an excellent tool to validate proteome analysis data.…”
Section: The Search For Mechanisms Involved In Pathogenesis: Proteomementioning
confidence: 99%